Presentation for Food Systems Transformation in Kenya: Lessons from the Past and Policy Options for the Future - Mbuthia, Juneweenex; Breisinger, Clemens (CGIAR, 2024)
Food systems transformation offers a promising avenue to achieve the goals Kenya has set out in the Bottom-Up Economic Agenda (BETA). The new book Food Systems Transformation in Kenya: Lessons from the Past and Policy Options for the Future, edited by Clemens Breisinger, Michael Keenan, Jemimah Njuki, and Juneweenex Mbuthia, takes a critical look at Kenya’s whole food system, including food supply chains, the food environment, consumer behavior, external drivers, and development outcomes and considers the system’s history and experiences from other countries. With chapters authored by Kenyan and international experts, this collaborative work presents both a bird’s-eye view of the Kenyan food system and in-depth analyses of its components. Rigorous economic research provides unique insights into both broad policy themes and specific actions that can position Kenya as a global leader in tackling the challenges of food-system-led transformation.